(untitled) (Global Journal of Human-Social Science, 2023)
This study assessed the Strategies for Improving Business Education Resources in Colleges of Education in Delta State Nigeria Four research questions and four hypotheses guided the study Survey research design was used in this study The population of the study was 122 Business Education lecturers from the three Colleges of Education in Delta State Stratified sampling technique was used to select 61 Business Education lecturers which represent 50 of the entire population based on strata i e 50 of Business Education lecturers from State 31 and Federal Colleges of Education 30